Theory of flight - Von Mises, Richard, 1883-1953 (Dover Publications, 1959)
Perhaps the most balanced, well-written account of fundamental fluid dynamics ever published. Mises' classic avoids the formidable mathematical structure of fluid dynamics, while conveying ? by often unorthodox methods ? a full understanding of the physical phenomena and mathematical concepts of aeronautical engineering. An outstanding textbook. ? Scientific, Medical and Technical Books.
"Unabridged and unaltered republication of the English translation first published ... in 1945."
Keywords: Aerodynamics.; Airplanes.; elektronické knihy; electronic books